Effect of Polylactic Acid on Mechanical, Chemical, Thermal, Morphology, Water Absorption, and Biodegradability Characteristics of Degradable Plastic from Durian Peel Waste - Medyan Riza; Sri Rahayu Retnowulan; Rozanna Dewi; Andre Yosi; Aldila Ananda; Rizka Nurlaila (Jurnal Kimia Sains dan Aplikasi, 2026)
Durian peels consist of cellulose, a potential base material for producing sustainable products, particularly degradable plastics. This study examines the impact of polylactic acid (PLA) blends on the degradable plastics derived from durian peel (Durio zibethinus). The mechanical characteristics of the degradable plastics: tensile strength of 2.5671–9.3498 MPa, elongation of 31–96%, and Young’s modulus of 161.32–219.95 MPa. The analysis of the compound revealed the presence of the alcohol monomer (O-H), alkanes and aromatic rings (C-H), carbonyl (C=O), and alkenes (C-O) groups. The potential for soil microbes to decompose these groups is also a consideration, given their hydrophilic nature, which enables them to bind to water. X-ray fluorescence (XRF) analysis of the degradable plastic sample revealed the presence of 13 elements: Mg, Ca, Al, P, Fe, Cl, K, Sr, Zn, Sc, Rh, S, and Si. In this study, no harmful metal contaminants (Pb, Hg, or Cd) were identified. Thermal analysis, encompassing a temperature range from 357.67°C to 443.67°C, has been instrumental in identifying the phase transition that marks the onset of extreme weight loss during crystallization. Morphological analysis revealed incomplete dissolution, leading to a nonuniform shape. Solubility is directly proportional to the duration of the stirring process. The degradable plastic with the least swelling is composed of 3.5 g of cellulose and 3 g of PLA, exhibiting a degree of swelling of 4.89%. The degradable plastic is predicted to decompose most rapidly after 56 days with a PLA content of 3 g. This experimental result aligns with the provisions outlined in ASTM D2096, a standard that establishes a maximum time limit of 180 days for the degradation of plastics.